REPRODUÇÃO E LONGEVIDADE DE Orius insidiosus (SAY) (HEMIPTERA: ANTHOCORIDAE) EM DIFERENTES TEMPERATURAS - Mendes, Simone M.; Bueno, Vanda H. P.; Carvalho, Lívia M. (REVISTA DE AGRICULTURA, 2015)
REPRODUÇÃO E LONGEVIDADE DE Orius insidiosus (SAY) (HEMIPTERA: ANTHOCORIDAE) EM DIFERENTES TEMPERATURAS